Relationships between physical activity, fitness level, body composition, and coronary heart disease risk factors in Malaysian and Arab adolescent students - Mehemed, Khaled Khalifa K. (2014)
The purpose of this study is to compare and further examine the relationships between lifestyle parameters (physical activity, body composition, fitness level) and coronary heart disease (CHD) risk factors of Arab and Malaysian adolescents. The study explores the differences in lifestyle parameters and CHD risk factors between Malaysian students studying in public and international schools. Participants were Malaysian students of public school and international school and Arab student of international schools in Klang Valley area, aged 14–16 years, and of both gender. Data was collated through use of questionnaires obtaining details of weekly physical activity (low, moderate, vigorous intensity). A 20m shuttle-run test was used to estimate the fitness level of participants (VO2max). The CHD risk factors were identified through measuring levels of high-density lipoprotein, low-density lipoprotein, non-high-density lipoprotein, total cholesterol, glucose and triglycerides by taking a fasting blood sample. Percentile body mass index (BMI) and percent body fat (%fat) were also measured.Descriptive statistics were conducted on physical activity levels, CHD risk factors, body composition, fitness level, dietary habits, sleeping duration, sedentary behavior, and five questions about exercise agenda. Prior to analysis, the assumptions of normality and homogeneity of variance/covariance were assessed. Normality was assessed with the examination of values of skew and kurtosis. Values of skew and kurtosis were within the appropriate parameters and the assumption of normality was met. The assumption of homogeneity of covariance was assessed with Box’s M andwas found to be significant (p <. 01). A Pearson product moment correlation matrix was conducted among the variables of interest to assess for multicollinearity among the dependent variables. A multivariate analysis of variance (MANOVA) and Analysis of Variance (ANOVA) were also conducted to assess the difference among the study variables and between groups. Results showed Malaysian adolescents at international schools had noticeably higher levels of fitness, high-density lipoprotein, and lower total cholesterol and body mass index and percent body fat than their colleagues at the public school. There is a significant relationship between BMI, %fat and CHD risk factors, than comparisons between fitness and physical activity level.Malaysian adolescents had higher triglycerides levels than Arab adolescents. Malaysian students at international schools are fitter and participate more in physical activity than the Malaysian adolescents at public schools. Furthermore, it was found that body composition is more of a predictor of CHD risk factors than fitness level or physical activity. Malaysian adolescents at public schools have a greater probability of developing CHD risk factors in the future.